The effect of think pair share method and students’ creativity on students’ learning outcome - Joni Indra Wandi; Azwar Ananda; Buchari Nurdin (Fakultas Ilmu Pendidikan UNP)
The aim of this study was to explore the effect of think pair share method and students’ creativity toward students’ learning outcome. This research was begun by doing the related surveys for current situation of social science in the history subject where teaching the subject did not provide yet the expected learning outcome. For that reason, it needed a think pair share method to strengthen students’ creativity in order to improve student’s learning outcome as well as their self-evaluation in enhancing their creativity and learning competence. This research used quantitative approach with survey method. The collection of the data used questionnaires, interviews, documentary studies, and field notes. Quantitative data were analyzed by using an experimental method. Data analysis used multiple linear regression and correlation test. The experimental results on the three classes showed that think pair share method and students’ creativity can improve students’ learning outcomebetter than conventional class, but there is no interaction between the think pair share method and creativity with the eighth grade students’ learning outcomes. Teacher could use this model to Junior High School students’ level for improving students’ learning outcome in the lesson of social science.